Pengembangan Aplikasi Augmented Reality Marker Based Tracking guna Meningkatkan Hasil Belajar Kendali Motor Listrik - Putri Andini Maulana; Suhendar Suhendar; Siswo Wardoyo (Jurnal Pendidikan Teknik Elektro, 2026)
Media in education acts as a tool to assist students in understanding the subject matter. Identifying and using the right kind of media can improve the effectiveness of students' learning. Observation data show that students do not understand electric motor control and have difficulty with practical work. Augmented reality is becoming an alternative technology in education to improve learning outcomes. This research aims to develop learning materials by integrating augmented reality with marker-based tracking. The ADDIE model is used as a method for analysis, modeling, improving implementation, and evaluation. Students following the Electrical Engineering study program in the State 4 Vocational High School of Serang City are subject to this study. Expert evaluation of media and content in Augmented reality learning media shows that it is categorized as "very appropriate". Additionally, student performance on the subject of electric motor control is assessed using the Wilcoxon method and N-gain, which reveals a statistically significant improvement after using Augmented reality-based learning media.